Male-biased Demand Shocks and Women's Labor Force Participation: Evidence from Large Oil Field Discoveries - Stephan Maurer; Andrei Potlogea (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We study whether male-biased demand shocks affect women's labor force participation (LFP), using major oil field discoveries in the US South between 1900 and 1940. We find that oil wealth has a zero net effect on female LFP due to two opposing channels. Increased male wages lead to a higher marriage rate of young women, which could have depressed female LFP. But at the same time, oil wealth also increases demand for female labor in services, which counterbalances the marriage effect.
Keywords: R11; N50; J12; J16; 330